Loss of Circulating CD8+ CD161high T Cells in Primary Progressive Multiple Sclerosis - Acquaviva, Massimo; Bassani, Claudia; Sarno, Nicole; Dalla Costa, Gloria; Romeo, Marzia; Sangalli, Francesca; Colombo, Bruno; Moiola, Lucia; Martinelli, Vittorio; Comi, Giancarlo; Farina, Cinthia (Frontiers in Immunology, 2019)
Recent evidence suggests that the primary progressive form of multiple sclerosis (PP-MS) may present with specific immunological alterations. In this study we focused our attention on CD161, an NK and T cell marker, and investigated its transcript and protein levels in blood cells from PP-MS and healthy individuals. We demonstrated transcriptional downregulation of CD161 in PP-MS and described concomitant mRNA reduction for RORgt, CCR6, CXCR6, KLRK1/NKG2D and many other markers typical of mucosa associated invariant T (MAIT) cells. Targeted multiparametric flow cytometry on fresh blood cells from an independent cohort of case-control subjects confirmed the selective loss of circulating CD8 CD161high T cells, which consist mainly of MAIT cells, and not of CD8 CD161int T cells in PP-MS. These data demonstrate alterations in a specific circulating immune cell subset in MS patients with progressive onset and suggest relocation of MAIT cells in the target organ.